Une modernité politique métropolitaine ? Impressions sensibles depuis Angers et Tokyo… - Alain Faure (Métropoles)
The exercise of metropolitan power immediately evokes symbols of domination and coercion, that is to say a certain form of world disenchantment. By studying what two elected metropolitan officials in Angers and Tokyo say about the sensitive motives of their engagement, we also catch a glimpse of an underground form of modernity, in gentleness for the first, in transgression for the second. The author of the article suggests that these two political promises deserve exploration.